Management of Digital Adab Education Through School–Parent Partnerships in Early Childhood Education - Asri Andriana Lituhayu; Rochmi Hastuti (Yayasan Azhar Amanaa Yogyakarta, 2026)
The rapid advancement of digital technology has created new challenges for Islamic educational institutions in managing technology use while maintaining children's character development. This condition requires educational management that not only emphasizes technology integration but also strengthens Islamic values through effective institutional governance. This study aims to examine the management of digital adab education based on school–parent partnerships in early childhood education from the perspective of Islamic Educational Management. A qualitative approach with a case study design was employed at RA Al Islamiyyah Kemayoran, Central Jakarta. Data were collected through interviews, observations, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings reveal three major themes. First, value-based Islamic management serves as the foundation for planning and implementing digital adab education. Second, school organizational culture functions as the primary mechanism for internalizing digital adab through role modelling, habituation, and consistent behavioural practices. Third, school–parent partnerships strengthen children's digital character formation through continuous communication, collaboration, and evaluation. This study proposes a conceptual model of digital adab education management grounded in Islamic values by integrating educational leadership, organizational culture, and school–parent partnerships as an institutional strategy for managing Islamic education in the digital era.